2011
DOI: 10.1186/1741-7015-9-6
|View full text |Cite
|
Sign up to set email alerts
|

Expenditures for the care of HIV-infected patients in rural areas in China's antiretroviral therapy programs

Abstract: BackgroundThe Chinese government has provided health services to those infected by the human immunodeficiency virus (HIV) under the acquired immunodeficiency syndrome (AIDS) care policy since 2003. Detailed research on the actual expenditures and costs for providing care to patients with AIDS is needed for future financial planning of AIDS health care services and possible reform of HIV/AIDS-related policy. The purpose of the current study was to determine the actual expenditures and factors influencing costs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 26 publications
(25 reference statements)
1
8
0
Order By: Relevance
“…This study also showed that for those living with HIV, the cost of laboratory tests accounted for the largest portion (37.46%) of associated in-patient costs, as those living with HIV may require semi-regular biochemical tests in order to track their disease progression while infected. Additional changes to current insurance policies, which promote reimbursement for laboratory tests could help lower patients' financial burden and promote compliance [15].…”
Section: Discussionmentioning
confidence: 99%
“…This study also showed that for those living with HIV, the cost of laboratory tests accounted for the largest portion (37.46%) of associated in-patient costs, as those living with HIV may require semi-regular biochemical tests in order to track their disease progression while infected. Additional changes to current insurance policies, which promote reimbursement for laboratory tests could help lower patients' financial burden and promote compliance [15].…”
Section: Discussionmentioning
confidence: 99%
“…In Thailand the mean cost to treat patients with TB/HIV was $1535 vs $6341 in Brazil 21. In China, TB was the most expensive opportunistic infection in PLHIV after Cytomegalovirus infection: $647 and $3189, respectively 22. In South Africa, the cost of hospitalised patients with TB/HIV was $3925.…”
Section: Discussionmentioning
confidence: 99%
“…To protect HIV households from catastrophic spending the most straightforward approach suggested by this study is to reduce major out of pocket expenses including transportation and hospitalization costs. Increasing early access to testing and ART would decrease hospitalization costs since here, most patients presented with very low CD4 levels and there is still a need to scale up ART coverage in the country [ 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%